Komunikasi Budaya K-Pop Masyarakat di Kampung Bali, Harapan Jaya, Bekasi Di Era New Normal - Edison Hutapea; Yuli Marlina (Communicology: Jurnal Ilmu Komunikasi, 2022)
Popular culture is a pattern of behavior that is preferred by most people. Appearance and style have become more important than morality, so the values of good or bad have been melted and overturned. Signs of the rapid influence of popular culture can be seen on consumptive Indonesian society. This happened due to foreign popular culture makes a person unaware of what is happening at that time. The researcher uses the hypodermic needle theory of communication in this study. Regarding the use of this theory is a process such as a mechanically rotating conveyor belt with clear elements, there are; a) the source (mediator), b) message (communicant), c) channel ( media), d) receiver (audience), and e) feedback (effect). In other words. This research used qualitative research procedure that produces descriptive data in the form of words, written or spoken words of people and observable behavior. By helping of social media, it has resulted in the dissemination of information about Korean culture in society, in this case a lot of people become fans of Korean culture for entertainment or to fill their spare time. Interaction between friends affects are able to spread the Korean culture, the interaction that occurs made people want to know more deeply and created a new sense of curiosity about Korean culture. With the existence of Korean culture, it also helps the community to survive through the crisis period that was occurred during pandemic.